The Shadows of Internationalisation: conceptual lens and policy perspectives - Shenderova, Svetlana; Jokila, Suvi; Anafinova, Saule; Liu, Yingxin (Margaret); Sharma, Harshita; Steane, Natalya (OsloMet - Oslo Metropolitan University, 2025)
This forum proposes the use of concept of “shadows” in the analysis of internationalisation policies to make visible the decision-making processes and practices appearing at all levels of internationalisation policies. We focus on the problematic effects appeared at the intersect of internationalisation policies implemented by the countries perceived academic values differently on example of Finland as the EU member state and pre-war Russia. We consider these effects as preventing equal access to quality higher education and life-long learning for all (SDG4, target 4.3). The forum conceptualises the lessons of the EU/Finnish-Russian internationalisation for further usage the suggested theoretical lens in policy implementation in other countries developed their own internationalisation policy on different value basis. This study address to what happens when the internationalisation policies promoted European view on fundamental academic values, are implemented with such policies in the countries where these values are perceived in another way. We answer the question of how and why the shadows of internationalisation appear and have an impact at a macro-, meso-, and micro-level, and conceptualize them for future policy improvement. The forum discusses the implications of internationalisation policies from the practice perspective and what might be learnt by the stakeholders previously involved in these cooperation partnerships.